Colorectal Perforation in Patients with Connective Tissue Disease - Kiichi Sugimoto; Kazuhiro Sakamoto; Yu Okazawa; Rina Takahashi; Kosuke Mizukoshi; Hisashi Ro; Masaya Kawai; Shingo Kawano; Shinya Munakata; Shun Ishiyama; Hirohiko Kamiyama; Makoto Takahashi; et al. (Emergency Medicine International)
Purpose. The goal of this retrospective study was to identify prognostic factors associated with mortality after surgery for colorectal perforation among patients with connective tissue disease (CTD) and to review postoperative outcomes based on these prognostic factors. Methods. The subjects were 105 patients (CTD group: n=26, 24.8%; non-CTD group: n=79, 75.2%) who underwent surgery for colorectal perforation at our department. Cases with iatrogenic perforation due to colonoscopic examination were excluded from the study. We retrospectively investigated perioperative clinicopathological factors in patients undergoing surgery for colorectal perforation. Results. There were 7 patients (6.7%) who died within 28 days after surgery in all patients. In multivariate analysis, CTD and fecal peritonitis emerged as significant independent prognostic factors (p=0.005, odds ratio=12.39; p=0.04, odds ratio=7.10, respectively). There were 5 patients (19.2%) who died within 28 days after surgery in the CTD group. In multivariate analysis, fecal peritonitis emerged as a significant independent prognostic factor in the CTD group (p=0.03, odds ratio=31.96). The cumulative survival curve in the CTD group was significantly worse than that in the non-CTD group (p=0.006). An analysis based on the presence of fecal peritonitis indicated no significant difference in cumulative survival curves for patients without fecal peritonitis in the CTD and non-CTD groups (p=0.55) but a significant difference in these curves for patients with fecal peritonitis in the two groups (p<0.0001). Conclusions. This study demonstrated that cumulative survival in patients with CTD is significantly worse than that in patients without CTD after surgery for colorectal perforation.